Formulasi Perkawinan Adat Lampung Dalam Bentuk Peraturan Daerah dan Relevansinya Terhadap Hak Asasi Manusia - Angkupi, Prima (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Regulation No. 2 of 2008 on maintenance of Lampung is a legal Culture Standing for indigenous peoples associated with regional legal instruments. Problems arise, when the shape of local regulatory policies that were originally intended to fight for the achievement of the traditional values and culture of the community is contrary to the spirit of extracting the values that live in the community itself. Article 16 paragraph (1) of Regulation No. 2 of 2008 on Maintenance Culture of Lampung, stating that the existence of Indigenous Culture Lampung about marriage, must be kept, maintained and developed. Larian in Lampung customary marriage is basically not feasible with the social conditions of Lampung today, because there is a change in the meaning of larian, which turned into a violation of law and violations of the constitutional rights of women. Larian marriage forms that ignore the girl's consent, is a violation of human rights and national marriage law. Therefore, the formulation of Article 16 of the Regulation on maintenance culture Lampung is unconstitutional.